Association of anticholinergic burden with adverse effects in older people with intellectual disabilities: an observational cross-sectional study. (December 2016) - O'Dwyer, Máire; Maidment, Ian D.; Bennett, Kathleen; Peklar, Jure; Mulryan, Niamh; McCallion, Philip; McCarron, Mary; Henman, Martin C.
Abstract : Background: No studies to date have investigated cumulative anticholinergic exposure and its effects in adults with intellectual disabilities. Aims: To determine the cumulative exposure to anticholinergics and the factors associated with high exposure. Method: A modified Anticholinergic Cognitive Burden (ACB) scale score was calculated for a representative cohort of 736 people over 40 years old with intellectual disabilities, and associations with demographic and clinical factors assessed. Results: Age over 65 years was associated with higher exposure (ACB 1–4 odds ratio (OR) = 3.28, 95% CI 1.49–7.28, ACB 5+ OR = 3.08, 95% CI 1.20–7.63), as was a mental health condition (ACB 1–4 OR = 9.79, 95% CI 5.63–17.02, ACB 5+ OR = 23.74, 95% CI 12.29–45.83). Daytime drowsiness was associated with higher ACB ( P <0.001) and chronic constipation reported more frequently (26.6% ACB 5+ v. 7.5% ACB 0, P <0.001). Conclusions: Older people with intellectual disabilities and with mental health conditions were exposed to high anticholinergic burden. This was associated with daytime dozing and constipation.